Developing Powerpoint Slide to Teach Modal Auxillaries Verbs Should and Must on Guiding Writing Simple Sentences in English (RETAIN, 2019)
Abstrak Menulis adalah kemampuan penting dalam bahasa inggris. Menulis terdiri dari pengetahuan, pengalaman, dan ide. Dalam kurikulum 2013, siswa di minta untuk membuat teks sebagai produk dari menulis. Siswa siswa kelas delapan mempunyai kewajiban untuk membuat kalimat sederhana menggunakan modal. Pada kenyataannya, siswa siswa tidak mengetahui bagaimana membuat sebuah kalimat yang baik menggunakan modal. Ini terjadi karena siswa kurang mengetahui grammar. Untuk menyelesikan masalah, penggunaan power point slide di butuhkan untuk membimbing siswa menulis. Penelitian ini bertujuan untuk mengembangkan power point slide untuk mengajar modal dan membimbing siswa menulis berdasarkan kesulitan siswa dalam belajar bahasa inggris. Modifikasi model penelitian dan pengembangan oleh (Dick, Carey, & O.Carey, 2015) untuk menjelaskan pengembangan dari power point slide. Berdasarkan hasil dari research, siswa merasa tertarik belajar melalui power point slide. Kata kunci: menulis, modal, R&D, and power point slide. Abstract Writing is an important skill in English. It consists of knowledge, experience, and ideas. In 2013 Curriculum, students are asked to create text as the product of writing. eight grades students have an obligation to make a simple sentence using modal auxiliaries. In fact, the students do not know how to make a good sentence using modal auxiliaries verbs. Knowing the students learning need, difficulty, and style are important to get good students’ outcome in learning. For solving the problem, the use of powerpoint slide is needed to guide the students writing. This study has a goal to develop a powerpoint slide to teach modal auxiliary and guide students writing based on the students’ difficulties in learning English. The modified research and development designs by (Dick, Carey, & O.Carey, 2015) to explain the development of a powerpoint slide. Based on this research, the students feel interested learning through powerpoint slide. Key words: writing; modal auxiliaries; R&D; and powerpoint slide.